Primary health care challenge for nursing professionals: a narrative review - Duran Niño, Erika Yurley; Campos de Aldana, María Stella; Arboleda de Pérez, Ligia Betty (Revista de Saúde Pública, 2021)
OBJECTIVE: Carry out a narrative review of scientific literature on nursing professionals training in primary health care (PHC), which allows us to know the challenges facing the renewal of this strategy. METHODS: Review of the literature found, selection of 55 articles from various scientific sources in the last 10 years in electronic databases (MEDLINE, IME, LILACS, Centro Cochrane Iberoamericano, Embase, CUIDEN, CINAHL, BDIE). The selected articles were submitted to an interpretation, synthesis, and critical analysis process for the purpose of selection. RESULTS: Higher education institutions in Colombia have been working on training of undergraduate students responding to the axes established in the strengthening of human resources in health. This training is used for the application of the integral health care model, focusing on the strengthening of work profiles and the acquisition of competencies that can generate significant contributions to the reality and needs of the individual, family, community, as well as to the different cultures and ethnic groups with humanization, under the general social security health system. An analysis of renewed and comprehensive PHC approaches has been carried out in different countries involving transformations in education with training by competencies, interprofessional work, teamwork, strengthening communication with the community, and health team. CONCLUSIONS: Based on the narrative review, this research highlights the importance of developing studies on interventions carried out by students with acquired competencies in their training process and management to improve health conditions of the community.